Nação - Sérgio Campos Matos (Ler História, 2008)
The concept of nation has undergone a profound change between 1750 and 1850, only understandable in the context of historical changes that occurred following the French invasion. If by 1808 it was not yet much used by the political elite (the words Kingdom and Monarchy were preferred), during the resistance to French occupation it is at some point asserted the principle of popular sovereignty. The Constitution of 1822 establishes the concept of sovereignty of the Nation and consecrates for the first time the doctrine of self-determination of the nation and its primacy regarding any law or authority. The word gets a central role in the political discourse of the first Liberalism. Now the term Kingdom loses protagonism (excluding in the realist, counter-revolutionary press). But in liberal political discourse, the concept of Nation, viewed as political association or independent totality of citizens or of the Portuguese as a whole, sometimes excluded several categories: the foreigners, men of faction (supporters of the Old political Regime) and, in some sense, the illiterate. For the Miguelists, the political opponents were also excluded from the national whole.